FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN PADA PEKERJA BURUH ANGKUT DI PASAR BALAI TANGAH KECAMATAN LINTAU BUO UTARA, SUMATERA BARAT - Puti Andam Dewi; Daru Lestantyo; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2019)
Fatigue means a condition where there is a decreased on someone’s performance because of some factors such as physical workload, length of work, age, and the sleep quality. Carrier in Balai Tangah Market have a complaints or fatigue symptoms like drowsiness, back pain, feeling dizzy and feeling heavy in the head, feeling thirsty, and excessive yawning. The purpose of this study was to analyze the factors (physical workload, length of work, age, sleep quality) related to fatigue at work. This type of research was quantitative with Cross-Sectional design. The population and sample in this study were 32 people. Fatigue at work data collection was carried out using the application of the deary-liewald reaction timer tester, pulse measurement using pulse oximetry, sleep quality measurement instruments using the pittsburgh sleep quality index (PQSI), and other data based on interview with respondents. Data analyzed using chi-square with α = 0,05. The results of the statistical test showed that there was correlation between length of work (p= 0,001) and sleep quality (p= 0,001). Whereas those who were unrelated were physical workload (p= 0,581) and age (p= 0,419).